Helmintofauna de duas espécies de anfíbios, Haddadus binotatus (Anura: Craugastoridae) e Ischnocnema guentheri (Anura: Brachycephalidae), da Mata Atlântica, no município de São Luiz do Paraitinga, São Paulo, Brasil - Nomura, Helen Akemi de Queiróz [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The Brazilian Atlantic Forest harbors a rich biodiversity with more than four hundred of amphibian species and many of these are endemic in this environment. This high rate of restricted endemism associated with global decline of amphibian diversity and density make it an important priority for the conservation of this ecosystem and to warrant intensive monitoring amphibian populations. Considering the importance that the parasites have on the ecology of their hosts, parasitic infections become a considerable factor in conservation biology. To expand the knowledge of this area, 23 specimens of Haddadus binotatus (Anura: Craugastoridae) and 36 Ischnocnema guentheri (Anura: Brachycephalidae) were collected from Santa Virginia, São Luiz do Paraitinga, São Paulo, between January and February 2010, to study their helminth parasites. Twelve helminth taxa were diagnosed and six of them were common to both hosts. The higher prevalence (P = 96%), mean abundance (MA = 11.7 ± 1.6) and mean intensity of infection (MII = 12.3 ± 1.6) were presented by H. binotatus compared to I. guentheri (P = 67%, MA = 2.4 ± 0.5, MII = 3.6 ± 0.6). Nematode species were found in different stages (cysts, larvae and adults) and acanthocephalans were found in both anurans. However, cestode species was found only in I. guentheri. Differences in parasitism of two species of frogs have been attributed to different sizes and micro-habitats of animals that allow different diets and contact with different helminth species. All helminths found have not been reported H. binotatus and also three new species records were noticed for I. guentheri

A Mata Atlântica abriga uma grande biodiversidade com mais de quatrocentas espécies de anfíbios anuros, sendo muitos desses endêmicos. Essa alta taxa de endemismo associado ao declínio global da diversidade de anfíbios tornam importante a prioridade para a conservação desse bioma e justificam o intenso monitoramento às populações de anfíbios. Sabendo da importância que os parasitas tem na ecologia de seus hospedeiros, as infecções parasitárias se tornam um fator considerável na biologia da conservação. Para ampliar os conhecimentos dessa área 23 espécimes de Haddadus binotatus (Anura: Craugastoridae) e 36 de Ischnocnema guentheri (Anura: Brachycephalidae) foram capturados no Núcleo Santa Virgínia, município de São Luiz do Paraitinga, São Paulo, entre janeiro e fevereiro de 2010 para o estudo de seus endoparasitas. Foram diagnosticadas 12 taxa de helmintos, sendo seis comuns aos dois hospedeiros. A maior prevalência total (P = 96%), abundância média (11,7 ± 1,6) e intensidade média de infecção (IMI = 12,3 ± 1,6) foram apresentadas por H. binotatus em comparação a I. guentheri (P = 67%; AM = 2,4 ± 0,5; IMI = 3,6 ± 0,6). Para as duas espécies foram encontrados nematódeos em diferentes estágios (cistos, larvas e adultos) e acantocéfalos. No entanto, apenas para I. guentheri foi encontrada uma espécie de cestódeo. Diferenças no parasitismo das duas espécies de anuros foram atribuídas à diferenças no tamanho corpóreo e uso de micro-hábitats pelos animais, que possibilitam dietas distintas e contato com diferentes espécies de helmintos. Nenhuma das espécies de endoparasita encontradas já havia sido descrita para H. binotatus e, além disso, foram realizados três novos registros de espécies para I. guentheri
Keywords: Parasitologia; Anuro; anfíbilio - Parasito; Biodiversidade